First Report on the Host Program: Pilot Projects in London, Winnipeg and Regina - Refuge Editor (Refuge: Canada's Journal on Refugees, 1986)
The objective of the host programme is to enhance the settlement process of those government-assisted refugees and other designated persons who qualify for support under the federal Adjustment Assistance Programme (AAP). This objective is to be achieved by matching these persons or families with host groups. The host groups are expected to assist refugees in settling more quickly. in learning English or French, in obtaining employment as soon as possible, and in providing friendship and emotional support. The Adjustment Assistance Programme currently provides funds to government-assisted refugees including those in the "control" programme. Funding is similar to provincial welfare assistance. Also allowances are paid to acquire basic clothing and furniture. This assistance is available to refugees for a maximum period of one year following arrival in Canada If, at some time during that period, the refugee becomes self-sufficient through employment, AAP funding ceases thereby.